IMPLEMENTASI KEBIJAKAN PERIZINAN USAHA BUDIDAYA PERIKANAN DI KABUPATEN BANDUNG - Putri, Kharisma; Sarihati, Tati (Jurnal Sosial Politik Unla, 2023)
This research is entitled " implementation of aquaculture business licensing policy in bandung district” This title is motivated by the existence of a problem, namely, there are still many aquaculture business actors who do not have licenses and cultivators do not know the importance of licenses. Researchers use Jones' policy implementation model theory in Agustino which includes the dimensions of Organization, Interpretation, and Application. Researchers formulated a proposition, namely the Implementation of the Aquaculture Business Permit Policy in Bandung Regency will run optimally if implemented based on the approach of organizational aspects, interpretation and application. The research method used is descriptive qualitative method. Data sources were obtained through observation, interviews and documentation. The informants in this study were the Food Security and Fisheries Service and the community of aquaculture business actors. In determining informants, researchers used purposive techniques. The results showed that the implementation of the aquaculture business license policy based on the Bandung Regency Regional Regulation on fish farming licensing has been running well, but still needs improvement in several aspects, such as inadequate human resources, uneven socialization of licensing, and the absence of assertiveness in imposing sanctions on business actors who do not fulfill aquaculture business obligations. For this reason, it is recommended that local governments optimize cooperation with the community so that the benefits and objectives of implementing local government policies on aquaculture business licenses can be carried out properly.